Modelling of energy storage dispatch for generation system adequacy studies. Issue 14 (1st November 2015) - Gafurov, Tokhir; Usaola, Julio; Prodanovic, Milan
Abstract : Energy storage systems (ESS) are expected to play an important role in future electricity networks and more modelling efforts are required to include them in generation system adequacy (GSA) studies based on sequential Monte Carlo simulations. This paper proposes a new, generic approach to ESS dispatch modelling that takes into account both technological and control aspects required for the simulation‐based GSA evaluations. The model features the application of detrended residual load that includes renewable production and distinguishes between different operating timescales. Moreover, by using the correction of ESS dispatch based on the classical proportional integral controller technique the model achieves a realistic representation of storage level variations. In this paper all the necessary model equations and parameter identification procedures are provided along with their underlying assumptions. The effectiveness of the new dispatch model is demonstrated by using a GSA study for a generation system comprising thermal power plants and hydroelectric ESS with annual and daily operating cycles.